IMPACT OF TEAM CREATIVITY ON SUSTAINABILITY OF LUBRICANT FIRMS IN ANAMBRA STATE (Journal of the Management Sciences, 2024)
In the dynamic business landscape of Anambra State, Nigeria, the sustainability of lubricant firms has become a critical imperative. This study examined the profound impact of team creativity on the sustainability of lubricant firms. Anambra State's business ecosystem is characterized by various challenges, including limited resources, regulatory complexities, and environmental concerns. In this context, sustainability is not just a buzzword but a strategic necessity. Additionally, the study explored the influence of leadership and organizational culture in fostering team creativity. The theoretical underpinning of this research lies in the Resource-Based View (RBV), emphasizing the significance of valuable, rare, inimitable, and non-substitutable resources and capabilities for competitive advantage. The study concludes that promoting team creativity can help lubricant firms overcome these challenges and thrive in a dynamic business environment. The findings highlight that team creativity plays a crucial role in driving innovation, problem-solving, enhancing customer experiences, and addressing environmental and social responsibilities. Recommendations included fostering a culture of curiosity and experimentation, creating cross-functional teams, implementing robust feedback mechanisms, and developing comprehensive sustainability strategies.
Keywords: Team creativity, sustainability, lubricant firms, Anambra State.